Immune escape pathways from the HBV core18-27 CD8 T cell response are driven by individual HLA class I alleles - Walker, Andreas; Schwarz, Tatjana; Brinkmann-Paulukat, Janine; Wisskirchen, Karin; Menne, Christopher; Alizei, Elahe Salimi; Kefalakes, Helenie; Theissen, Martin; Hoffmann, Daniel; Schulze zur Wiesch, Julian; Maini, Mala K.; Cornberg, Markus; et al. (Frontiers in Immunology, 2022)
Background and aims There is growing interest in T cell-based immune therapies for a functional cure of chronic HBV infection including check-point inhibition, T cell-targeted vaccines or TCR-grafted effector cells. All these approaches depend on recognition of HLA class I-presented viral peptides. The HBV core region 18-27 is an immunodominant target of CD8+ T cells and represents the prime target for T cell-based therapies. Here, a high-resolution analysis of the core18-27 specific CD8+ T cell and the selected escape pathways was performed. Methods HLA class I typing and viral sequence analyses were performed for 464 patients with chronic HBV infection. HBV-specific CD8+ T-cell responses against the prototype and epitope variants were characterized by flow cytometry. Results Consistent with promiscuous presentation of the core18-27 epitope, antigen-specific T cells were detected in patients carrying HLA-A*02:01, HLA-B*35:01, HLA-B*35:03 or HLA-B*51:01. Sequence analysis confirmed reproducible selection pressure on the core18-27 epitope in the context of these alleles. Interestingly, the selected immune escape pathways depend on the presenting HLA-class I-molecule. Although cross-reactive T cells were observed, some epitope variants achieved functional escape by impaired TCR-interaction or disturbed antigen processing. Of note, selection of epitope variants was exclusively observed in HBeAg negative HBV infection and here, detection of variants associated with significantly greater magnitude of the CD8 T cell response compared to absence of variants. Conclusion The core18-27 epitope is highly variable and under heavy selection pressure in the context of different HLA class I-molecules. Some epitope variants showed evidence for impaired antigen processing and reduced presentation. Viruses carrying such escape substitutions will be less susceptible to CD8+ T cell responses and should be considered for T cell-based therapy strategies.